PENGARUH GOOD CORPORATE GOVERNANCE TERHADAP MANAJEMEN LABA DENGAN TAX PLANNING SEBAGAI VARIABEL INTERVENING PADA PERUSAHAAN MANUFAKTUR SUBSEKTOR TEKSTIL DAN GARMENT YANG TERDAFTAR DI BEI PERIODE 2016-2020 - Rizkia, Linda; Sari, Lita Permata; Subaida, Ida (Fakultas Ekonomi dan Bisnis, 2022)
Profit management is an activity carried out by the company's management to manipulate profit figures in the company's financial statements. Profit management is a system that managers logically do to change the value of profits and is designed using evaluation methods. The purpose of changing accounting techniques and accounting procedures is to benefit from different parties. Profit is one of the important elements in financial statements used to measure management performance. Profit is one of the important elements in financial statements used to measure management performance. The purpose of this study is to analyze and test the influence of Good corporate governance on profit management through Tax planning. The population in this study is manufacturing companies of the Textile and Garment sub-sector. The semple retrieval technique was determined by puposive sampling. Data analysis and hypothesis testing in this study used the Structural Equation Model – Partial Least Square (PLS-SEM). The results of the hypothesis test of direct influence using the Smart PLS 3.0 application, showed that Good corporate governance has a significant effect on Tax planning, Good corporate governance does not have a significant effect on profit management, Tax planning has a positive but not significant effect on profit management. . The results of the hypothesis test of indirect influence show that the variable Good corporate governance on profit management through Tax planning has a positive but not significant effect.